WORLD EXPERIENCE AND APPLICATION OF DRIP IRRIGATION TECHNOLOGIES IN UZBEKISTAN (British Journal of Global Ecology and Sustainable Development, 2025)
The article is devoted to research on drip irrigation and other irrigation methods in countries such as the USA, Germany, Russia, Australia, Israel, etc. The experience of using drip irrigation in Uzbekistan is considered, taking into account soil properties and with the use of a controlled automatic electronic drip irrigation system.